HARMONI AGAMA DAN BUDAYA: KAJIAN LIVING QUR’AN TRADISI LOLOBARAN AGUNG MASYARAKAT MADURA - Rifqatul Husna; Qurratul Layyinah (LPPM STAI Muhammadiyah Probolinggo, 2025)
The concept of Living Qur'an emphasizes the implementation of Qur'anic teachings in daily life, not just reading and memorizing activities, by adjusting Qur'anic values to the local cultural context. This research examines the tradition of Lolobaran Agung in Dusun Panggung, Sumenep, as one of the Living Qur'an phenomena. This tradition integrates the recitation of the Qur'an, tahlil, joint prayer, and interpretation of Surah Az-Zumar verses 71-75 with local wisdom inherited from the ancestors. Through Emile Durkheim's social fact theory and mechanical solidarity approach, this tradition is analyzed as a collective practice that strengthens social relations, builds collective awareness, and preserves local cultural identity. This research shows that Lolobaran Agung is not only a spiritual means to strengthen faith, but also a tool to face the challenges of globalization by maintaining religious values and local culture. This research uses a qualitative method with an ethnographic approach to analyze the Living Qur'an phenomenon in the context of the relationship between religion, tradition and society. In addition, this research expands the scope of Living Qur'an studies through a socio-cultural perspective that highlights the dynamics of the interaction of the three.